what is 1/10 divided by 9/10?
Answer:
1/10 divided by 9/10 is 1/9
Step-by-step explanation:
It is 1/9 because 1/10 divided by 9/10 is the same as using the reciprocal of 9/10 which then now you have 1/10 multiply by 10/9 and you have 10/90 which is simplified to 1/9.
Hope this helps. :)
2.14 (.14 being repeated) = ?
Simplified fraction of 2.14(.14 being repeated) is 212/99.
A fraction is said to be in its simplified if the fractions in their lowest, reduced and simplest form.
Now the given fraction is 2.141414....
Let x = 2.14141414.... -------- (1)
Multiply by 100 on both sides.
100x = 214.141414....
100x = 214.141414... -------- (2)
Subtract (1) from (2),
100x - x = 214.141414... - 2.14141414....
99x = 212
Divide by 99 on both sides, we get
x = 212/99
Hence the simplified fraction is 212/99
More about simplified fraction:
#SPJ2
Answer:
Step-by-step explanation:
We require 2 equations with the repeated part after the decimal point. Then subtract them to eliminate the repeating part.
let x = 2.1414... (1) ← multiply both sides by 100
100x = 214.1414... → (2)
Subtract (1) from (2)
100x - x = 214.1414 - 2.1414, that is
99x = 212 ( divide both sides by 99 )
x =
That is 2.1414... =
The relationship between the two triangles can be described as ΔMLN ~ ΔFGH by the third angle theorem, ∠M ≅ ∠F, ∠L ≅ ∠G, and ∠N ≅ ∠H.
Given two triangles.
The triangles are named as LMN and FGH.
Also, two of the angles of each triangle is given.
For triangle LMN,
∠L = 36° and ∠M = 51°
Similarly, for triangle FGH,
∠G = 36° and ∠F = 51°
So, for both triangles,
∠L = 36° = ∠G
∠M = 51° = ∠F
Using the angle sum property of triangles,
∠N = ∠H = 180° -(36° + 51°) = 93°
That is, all three angles of triangle LMN is equal to triangle FGH.
So, by the third angle theorem, ΔMLN is similar to ΔFGH.
Hence, the correct option is A.
Learn more about Similar Triangles here :
#SPJ2
Answer:
Just took the test test it is A 100%
Step-by-step explanation:
Answer:
33
Step-by-step explanation:
i don't know the step by step explanation so sorry for that
10.7a Plus 27.7b
18.1a Minus 8.1b
18.1a Plus 27.7b
So,therightanswerisofoptionA.
Lookattheattachedpicture⤴
Hopeitwillhelpu...
Answer:
a
Step-by-step explanation:
Answer:
x = - 3, x =
Step-by-step explanation:
Given
f(x) = 4x² + 5x - 21
To obtain the zeros, equate f(x) to zero, that is
4x² + 5x - 21 = 0
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term
product = 4 × - 21 = - 84 and sum = + 5
The factors are + 12 and - 7
Use these factors to split the x- term
4x² + 12x - 7x - 21 = 0 ( factor the first/second and third/fourth terms )
4x(x + 3) - 7(x + 3) = 0 ← factor out (x + 3) from each term
(x + 3)(4x - 7) = 0
Equate each factor to zero and solve for x
x + 3 = 0 ⇒ x = - 3
4x - 7 = 0 ⇒ 4x = 7 ⇒ x =
You can find the zeros of the function f(x) = 4x² + 5x - 21 by setting the function equal to zero and solving for x using the quadratic formula. Upon solving, you get the zeros as -7/4 and 3.
To find the zeros of the quadratic function f(x) = 4x² + 5x - 21, you need to set the function equal to zero and solve for x. This means solving the equation 4x2 + 5x - 21 = 0. This is a quadratic equation that can be solved using the quadratic formula, x = [-b ± √(b² - 4ac)] / (2a).
Here, a = 4, b = 5, and c = -21. Substituting these values into the quadratic formula gives us x = [-5 ± √((5)² - 4*4*(-21))] / (2*4). Simplifying yields x = {-7/4, 3}.
#SPJ2